2023
DOI: 10.3390/jcm12020647
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Postpartum Maternal Functioning in Black Women: A Secondary Analysis

Abstract: In the United States, 29–44% of Black women experience postpartum depressive symptoms (PDS), yet few are properly identified and/or connected to mental care services. The purpose of this secondary analysis was to examine the relationship between maternal functioning and clinical variables (PDS, maternal–infant attachment), racial variable (Black racial identity types—low race salience, assimilated and miseducated, self-hating, anti-White, multiculturalist, and conflicted), and sociodemographic characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Yet in the present study participants self-reported having no mental health issues. This is significant, as maternal performance is known to increase where the severity of depression is reduced and overall mental health is improved [26,33]. In the present study, the highest score related to the domain of 'maternal competence' was similar to results reported elsewhere in Iran [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Yet in the present study participants self-reported having no mental health issues. This is significant, as maternal performance is known to increase where the severity of depression is reduced and overall mental health is improved [26,33]. In the present study, the highest score related to the domain of 'maternal competence' was similar to results reported elsewhere in Iran [34].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, participants who had a higher level of education performed better than participants who had only primary education. In another study, participants with less education also demonstrated poorer performance [46], and in two other studies, the level of education had a positive and significant relationship with maternal performance, where those who had a higher level of education demonstrated enhanced maternal performance [31,33]. In other studies, there was a significant relationship identified between participant occupation and maternal performance [34].…”
Section: Discussionmentioning
confidence: 92%
“…(15), include negative views of PPD from partners, family and friends. Gender identity, racial identity, and class may make some women uniquely susceptible to facing discrimination from others, which may increase the likelihood and severity of PPD symptoms and negatively impact help-seeking (24). A lack of emotionally warm and empathetic support can also be detrimental to seeking mental health treatment.…”
Section: Figurementioning
confidence: 99%